2013
DOI: 10.1097/ta.0b013e3182988b1f
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic shock and resuscitation are associated with peripheral blood mononuclear cell mitochondrial dysfunction and immunosuppression

Abstract: BACKGROUND Trauma and hypovolemic shock are associated with mitochondrial dysfunction and septic complications. We hypothesize that hypovolemic shock and resuscitation results in peripheral blood mononuclear cell (PBMC) mitochondrial dysfunction that is linked to immunosuppression. METHODS Using a decompensated shock model, Long-Evans rats were bled to a MAP of 40 mmHg until the blood pressure could no longer be maintained without fluid infusion. Shock was sustained by incremental infusion of Lactated Ringer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 38 publications
(62 reference statements)
1
36
0
1
Order By: Relevance
“…Since then, improvements in hospital hygiene have reduced combat deaths from infectious disease, but an equivalent phenomenon persists [2,3]. Sterile trauma due to major surgery or closed injury increases vulnerability to pneumonia, urinary infection, alimentary infection, sepsis and multi-organ failure, and these outcomes are exacerbated by haemorrhage, transfusion and ageing [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, improvements in hospital hygiene have reduced combat deaths from infectious disease, but an equivalent phenomenon persists [2,3]. Sterile trauma due to major surgery or closed injury increases vulnerability to pneumonia, urinary infection, alimentary infection, sepsis and multi-organ failure, and these outcomes are exacerbated by haemorrhage, transfusion and ageing [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with sepsis, reduced oxygen consumption and lower mitochondrial membrane potential in PBMCs have been associated with disease severity, immune dysregulation, and decreased survival (11,12). In a recent study, we have also observed that mitochondrial function is altered in PBMCs following hemorrhagic shock and resuscitation in a rodent model (13). Similar to a report by Belikova et al (12), we found that PBMCs recovered mitochondrial function when incubated in serum from control animals with control PBMCs developed depressed function when incubated with serum collected following severe shock; suggesting a systemic factor may be responsible for mitochondrial dysfunction in PBMCs.…”
Section: Introductionmentioning
confidence: 82%
“…In particular, PBMC respiratory function may reflect disease severity in sepsis (12) and we have noted that PBMC mitochondrial function is dramatically altered during hemorrhagic shock and resuscitation (13). As such, monitoring PBMC respiratory capacity may provide a minimally invasive surrogate for end-organ mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…The rat model of hemorrhagic shock was constructed based on Chaudry's method (Villarroel et al, 2013) with some modifications. The rats were anesthetized by intraperitoneal injection of pentobarbital sodium (40 mg/kg) and immobilized on a 25°C heating plate using 500 U/kg heparin anticoagulation.…”
Section: Construction Of Rat Model Of Hemorrhagic Shockmentioning
confidence: 99%
“…Although the short-term survival of patients after resuscitation increases, the long-term mortality is still high, which may be attributed to the resulting immunological stress and inflammatory response. Different fluid resuscitation techniques may have different effects on the immune response after hemorrhagic shock (Gao et al, 2009;Gao et al, 2013;Villarroel et al, 2013;Cheng et al, 2014). Myeloid cells, first discovered in tumor patients, play a negative regulatory role in the immune system and have recently acquired the collective term myeloid-derived suppressor cells (MDSCs) (Krystal et al, 2007).…”
Section: Introductionmentioning
confidence: 99%